A randomized controlled trial of ivabradine in patients with acute myocardial infarction related cardiogenic shock - Alcaraz-Guzmán, Alejandro (2024)
Objective. Acute myocardial infarction-related cardiogenic shock (AMI-CS) is often accompanied by tachycardia, which, in turn, increases myocardial oxygen consumption and hinders the use of ventricular assist devices, such as intra-aortic balloon pump. Evidence suggests that ivabradine may reduce heart rate (HR) without affecting other hemodynamic parameters. The aim of the present study was to determine the effect of ivabradine on reducing HR and changes in other hemodynamic parameters such as cardiac index (CI), in patients with AMI-CS and tachycardia. Materials and methods. A single-center, open label, randomized clinical trial included patients diagnosed with AMI-CS and tachycardia with >100 beats per minute (BPM). Heart rate, cardiac index, and other hemodynamic parameters measured by pulmonary flotation catheter were compared at 0, 6, 12, 24, and 48 hours after randomization. Results. A total of 12 patients were randomized; 6 received standard therapy, and 6 received ivabradine in addition to standard therapy. Baseline clinical characteristics were similar at randomization. A statistically significant lower heart rate was found at 12 hours (p=0.003) and 48 hours (p=0.029) after randomization, with differences of -23.3 (-8.2 to -38.4) BPM and -12.6 (-0.5 to -25.9) BPM, respectively. No differences in cardiac index, or any other evaluated hemodynamic parameters, length of hospital stay, nor mortality rate were noted between both groups. Conclusions. The use of ivabradine in patients with AMI-CS was associated with a significant reduction in heart rate at 12 and 48 h, without affecting other hemodynamic parameters.